2020
DOI: 10.1182/blood.2020005895
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor–dependent DNA repair promotes murine and human hematopoietic regeneration

Abstract: Chemotherapy and irradiation cause DNA damage to hematopoietic stem cells (HSCs), leading to HSC depletion and dysfunction and risk for malignant transformation over time. Extrinsic regulation of HSC DNA repair is not well understood and therapies to augment HSC DNA repair following myelosuppression remain undeveloped. We report that epidermal growth factor receptor (EGFR) regulates DNA repair in HSCs following irradiation via activation of the DNA-dependent protein kinase - catalytic subunit (DNA-PKcs) and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…Although it is still unclear how RPRM regulated the expression of EGFR and its phosphorylation, which needs further study, these results are in agreement with a recent report that EGFR regulates DNA repair in HSCs following irradiation via activation of DNA-PKcs (Fang et al, 2020). Interestingly, our results also suggested that EGFR Our study also suggests that RPRM deletion promotes HSC survival through the EGFR-STAT3-Lin28a pathway.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although it is still unclear how RPRM regulated the expression of EGFR and its phosphorylation, which needs further study, these results are in agreement with a recent report that EGFR regulates DNA repair in HSCs following irradiation via activation of DNA-PKcs (Fang et al, 2020). Interestingly, our results also suggested that EGFR Our study also suggests that RPRM deletion promotes HSC survival through the EGFR-STAT3-Lin28a pathway.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to promoting DNA‐PKcs activation and increasing Xrcc6 expression, our study suggested that RPRM deletion increased the expression levels of EGFR and p‐EGFR in irradiated HSCs. Although it is still unclear how RPRM regulated the expression of EGFR and its phosphorylation, which needs further study, these results are in agreement with a recent report that EGFR regulates DNA repair in HSCs following irradiation via activation of DNA‐PKcs (Fang et al, 2020 ). Interestingly, our results also suggested that EGFR and DNA‐PKcs formed a feedback loop to regulate DNA repair since inhibiting DNA‐PKcs activation could significantly downregulate the expression of EGFR and p‐EGFR confirming the reciprocal relationship between DNA‐PKc phosphorylation and EGFR‐mediated radiation response (Javvadi et al, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…7F). EGF signaling has also been implicated in maintaining genomic integrity in hematopoietic stem cells (48). We therefore assessed γ-H2AX levels in inducible…”
Section: Mettl3 Deletion Reduces Kras Methylation and Protein Express...mentioning
confidence: 99%
“…Likewise, EGF showed to activate the expression of human telomerase reverse transcriptase in cultured cells, via Ets-2, a cancerspecific transcription factor that appears to depend on EGF receptor (EGFR)-mediated Erk and Akt activation [115]. Experimental studies suggest that EGF enhances cell survival and tissue replenishment in otherwise lethal scenarios, by controlling oxidative stress and by mitigating cellular senescence [116][117][118][119].…”
Section: Egf Biological Effects To Counteract Dfu Chronicitymentioning
confidence: 99%